Pengaruh Penambahan Abu Terbang Terhadap Kekuatan Beton - Efrizal, Eki (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2015)
The addition of fly ash in concrete mix can be very important when sufficient compressive strength needed early while the fly ash to be used. Therefore, it is necessary to study its effect on the strength of just two types namely tensile strength and compressive strength of concrete. In this study, made 4 cylinder variation of the test specimen measuring 150 mm x 300 mm. Each variation is represented by 24 samples with details 18 pieces for compressive strength test and 6 pieces for tensile strength test. The first variation is made without adding fly ash and used as a comparison against other variations. Variations second, third and fourth made by adding fly ash as much as 5%, 10%, and 15% by weight of cement. Compressive strength test performed at 14 days, 28 days and 56 days. Tensile strength test is only performed at 28 days. Compressive strength test results showed that each percent increase fly ash cause a decrease in the compressive strength at 14 and 28 days. After reaching the age of 56 days, the test object with the addition of fly ash will have a greater compressive strength dabanding not using fly ash, with the addition of optimum as much as 10% of the weight of the cement. Results of tensile strength tests at 28 days showed that the addition of fly ash concrete will have a tensile strength greater than that not using fly ash. Tensile strength values ranged from 10% to 12% of the value of compressive strength. The relationship between tensile strength and compressive strength without the addition of fly ash at 28 days in the range of fct = (6-7) x√f'c, but when fly ash is added the association constants will exceed the value 7.